Medetera (Diptera, Dolichopodidae) of Sri Lanka - Naglis, Stefan; Bickel, Daniel J. (Zootaxa, 2012)
The following five species of Medetera are described as new from Sri Lanka: M. peradeniya, M. kandyensis, M. colombensis, M. nuwarensis, M. subgrisescens. A key is provided to males of the ten known Sri Lankan species of Medetera.